(untitled) (UNED Research Journal, 2015)
The giant African snail is currently one of the most aggressive and invasive species that has colonized many countries outside its natural environment. We recorded four shell measures and the weight of 3 157 individuals of Achatina fulica collected in Boyacá, Cundinamarca, Meta, Norte de Santander and Valle del Cauca, Colombia. Larger and heavier individuals were collected in the Meta and Boyacá departments while the highest density per square meter was recorded in Cundinamarca. We found a strong, positive and highly significant (p<0.01) correlation among measured variables. During development maximum sizes of shell, opening and body weight are correlated, and shell length increases faster than the other measures, leading to a marked elongation of the individuals. The settling time of the populations was also reflected in the size of individuals.